Graphic Design Training Using Photoshop Software as a Business Opportunity - Rofiqoh Dewi; Wiwi Verina; Muhammad Barkah Akbar (JUDIMAS, 2021)
Graphic Design is currently one of the few software that has been widely used for the development of knowledge because it is very easy to use in various aspects of work. Jobs by utilizing graphic design have a very large opportunity to be used by students with the current pandemic conditions, because apart from being easy to use in basic work for students, many social media users such as Instagram and Facebook want good Instagram and Facebook feeds. For this reason, it is inevitable that many social media users need photo editing services such as graduation photo editing and travel photo editing so that it can be used as a business opportunity among students to take the job because the work can be done anywhere with easily accessible tools. In today's world of work, if human resources (HR) do not have additional abilities or skills, it will be difficult to compete in obtaining work. Through this introduction, students are also expected to get to know the tools that exist in Photoshop software. With the introduction of Photoshop, it is hoped that it can provide new insights and knowledge to the students of Budi Agung Medan Private High School about making graphic design as a business opportunity.